CROWDSOURCING: ARSIP, MEMORI KOLEKTIF, DAN ERA DIGITAL: Array - Harry Bawono (Jurnal Kearsipan, 2019)
Since 2012, National Archives of Indonesia has been developing National Archival Information System (SIKN) and National Archival Information Network (JIKN). Both platform provide easier access to archival records and in turn connect the local archives as their hubs. Crowdsourcing enriches the networks and increasing societal participation. This research had been conducted from January to April 2019 by using qualitative methods through interviews. This article argues that crowdsourcing is very helpful for adding archival collection.